A comparison of placental pathology between small for gestational age infants at < 5 % versus 5–9 %. (September 2020) - Sandlin, Adam T.; Magann, Everett F.; Ounpraseuth, Songthip T.; Hammad, Ibrahim A.; Goodier, Christopher G.; Thagard, Andrew S.; Dahlke, Joshua D.; Chang, Eugene Y.; Quick, Charles M.; Chauhan, Suneet P.
Highlights: SGA infants < 5 % vs. 5−9 % have greater perinatal morbidity and mortality. SGA infants < 5 % vs. 5−9 % have significantly decreased placenta weights. Placental pathologic features were similar between SGA infants <5 % vs. 5−9 %. Abstract: Introduction: Among SGA newborns, those < 5th % for GA are more likely to have adverse outcomes than those at 5−9th %. The differential morbidity and mortality may be due to abnormal placental pathology between groups. Our purpose was to compare placental pathology characteristics and composite placental pathology among SGA infants with birth weights <5th % vs. 5−9th %. Methods: This study is a secondary analysis of a multicenter, retrospective cohort study. Placental pathological variables and composite placental pathology (CPP) among SGA infants <5th % and 5−9th % were compared. Multivariable logistic regression was used to model the probability of an infant's birth weight being classified as <5th % based on pathology characteristics. Results: Of 11, 487 live singleton births, 925 SGA infants met inclusion criteria. Placental pathology was available for review in 407 (44 %) SGA infants: 210 (51.6 %) <5th % and 197 (48.4 %) 5−9th %. A decreased placental weight for GA, was more common in the <5th % group compared to the 5−9th % group (p = 0.0019). No significant differences in the distribution of pathological variables or in CPP (p = 0.3) was observed between the two centile groups. A decreased placental weight was the only reliable predictor of an infant's birth weight centile group (p = 0.0018). Conclusions: Placental hypoplasia, reflected by a decreased placental weight for GA, was significantly more common among SGA infants < 5th % compared to the 5−9th %. There was no difference in placental pathological features or CPP between the two centile groups of SGA infants.